The Hidden Danger in Digital Children Games: Gambling - Erdal, Kelime; Erdal, Gultekin (Journal of History Culture and Art Research, 2020)
The history of gambling is linked and proportionate to the history of humanity. No matter how far you go back in human history, remnants show that gambling groups have come together, and gambling games are taking place. In digital children games, gambling will and albeit somehow, by paying different costs. Because technology has become an integral part of our lives and the age of using technology has dropped until the preschool age. This may raise concern in terms of gambling, although not for every digital game. With this article, the reason for the danger in digital children's games, the proportion of existing digital games with computer addiction, not by directly targeting the names and brands, was investigated. Because the danger of gambling can occur in any game, in any way, and at unexpected costs. To get to the root of the problem, it was investigated why people spend time at the computer and why they want to earn. However, as the theories revealing the causes of digital children's games also show, gamers are unaware of the gambling danger of many games. When a desire for addiction is combined with the person's urge to show up, the face of invisible danger, gambling appears. With this research, the obvious danger of technology and internet addiction has been taken into consideration as well as gambling, which is a hidden danger. In addition to the devotion of individuals to digital games, their time spent in front of the computer and is unhealthy environments were also examined. Results were tried to be reached in line with the findings obtained.